”Ni är inte välkomna i vårt fina Malmö”: Premisser för samhällsgemenskap i kamp mot organiserad brottslighet (Sociologisk Forskning, 2015)
”You are not welcome in our lovely Malmo”: Conditions for belonging in mobilization against organized crime Several murders occurred in the Swedish city of Malmö between 2011 and 2012. Against this backdrop, the municipality and the police initiate a public campaign. The aim is to mobilize the city’s population against organized crime. In this study the ideology of the initiative is analysed. It is argued that the representation of organized crime as nurtured by the black economy can be read as an example of neoliberal revanchist city agenda, albeit an ambivalent one. The role of groups working in the low-price sphere of the economy becomes that of a threatening projection, while a consumption ideology regulates the boundaries of belonging
Keywords: belonging; black economy; crime prevention; organized crime; revanchist city